Adapted cavotomy technique for pheochromocytoma associated tumor thrombi in a dog - de Andrade, Caroline Ribeiro [UNESP]; Barboza, Wendell Monteiro; Silva Lessa, Diego Fernando; dos Santos Malta, Caio Afonso [UNESP]; Cabral, Rosa Maria (Universidade Federal do Rio Grande do Sul, 2020)
Background: In dogs pheochromocytoma usually compress and invade into the adjacent vessels and structures, which may lead to the occurrence of caudal vena caval tumor thrombi. The surgical approach in these cases requires adrenalectomy with caval thrombectomy. Conventionally, tourniquets and partial occlusion clamp are used to reduce intraoperative blood loss, but in dogs with a large thrombus associated to a great local tumor invasion, the traditional technique may be hindered. The aim of this study was to report the use of a purse-string suture during venotomy of the caudal vena cava for thrombectomy, as an alternative to tourniquet and partial occlusion clamp. Case: An 11-year-old male Daschound breed dog, was referred for evaluation because of the appearance of small blackened nodules in the ventral abdomen. During a search for metastatic lesions with abdominal ultrasound, the right adrenal was identified with significant volume increase, and presence of tumor-associate circular formation that appeared to invade the caudal vena cava, suggestive of neoplastic invasion or thrombus. Abdominal computed tomography showed caudal vena cava in its hepatic portion presenting considerable increase in diameter, with caudal dilation and presence of hypoattenuating material in its lumen. Right adrenal gland with rounded appearance and regular borders, heterogeneous parenchyma and juxtaposed caudal vena cava suggesting invasion of this, confirming the sonographic findings. During exploratory celiotomy, adherence of the adrenal mass to the right renal vessels and invasion of the caudal vena cava were observed, leading to the need of nephrectomy and venotomy for thrombectomy. To perform the venotomy, a Rumel tourniquet was placed loosely around the vena cava only caudal to the invasion point of the tumor thrombus, cranially, tourniquet application was not possible due to the presence of a large thrombus extending into the intrahepatic cava. Therefore, a purse-string suture was applied around the invasion point of the vena cava tumor thrombi. Thus, during the thrombectomy, while dissecting with the scalpel blade, the purse-string suture was gently tightened, minimizing hemorrhage and allowing the venotomy to close immediately after thrombi removal. Histopathological mass analysis allowed the diagnosis of malignant pheochromocytoma with intravascular extension of the tumor, and the patient remained without clinical changes for 18 months. Discussion: When caval invasion by the adrenal mass is present, the application of Rumel tourniquets around the vena cava cranial and caudal to the tumor thrombus invasion point is recommended to reduce intraoperative hemorrhage during thrombectomy. However, due to the presence of a large thrombus extending into the intrahepatic cava in the presente report, it was not possible to apply the cranial tourniquet, just the caudal one. Thus, the technique adapted using a purse-string suture during venotomy of the caudal vena cava for thrombectomy was extremely efficient in controlling hemorrhage, while allowing rapid venotomy closure without the need for partial occlusion vascular clamp, reducing the surgical time. A tumor thrombus in the vena cava associated with adrenal gland tumors are amenable to adrenalectomy and thrombectomy without significantly increasing perioperative morbidity and mortality rates, assuming the surgeon is experienced in appropriate techniques. Moreover, the presence of tumor invasion does not seem to be predictive of the outcome of the cases, in agreement with what happened in this case.
Uso de técnica adaptada para cavotomia em cão com feocromocitoma associado a trombo neoplásico
Keywords: Adrenal neoplasm; Purse-string suture; Venotomy